225k views
5 votes
Solve 2(y – 3) = 1.2 – y.

User BCsongor
by
7.5k points

2 Answers

4 votes
first write down your equation. 2(y-3)=1.2-y. the distribute your 2. 2 times y is 2y and 2 times -3 is -6. now you have 2y-6=1.2-y. bring your y to the other side of the equation with the opposite sign and do the same with your 6. you have 2y+y=1.2+6. combine the like terms and constants. now you have 3y=7.2. divide bother sides of the equal by 3 to get y alone. 3y/3= 7.2/3. your answer is y=2.4.
User Disperse
by
7.3k points
3 votes

Answer:y=2.4

Explanation:

Given the expression

2(y – 3) = 1.2 – y

Opening thee bracket

2y-6=1.2-y

Colleting like terms

=2y+y=1.2+6

3y=7.2

Dividing both sides by 3

3y/3=7.2/3

Y=2.4

User Babsdoc
by
6.8k points